The Impact of Fixed Asset Revaluation and Depreciation Methods on the Financial Statements of PT Panca Putera Galvalum Steel - Rosalia anggi Barimbing; Ninik Anggraini; Muhammad Alfa Niam (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the effect of fixed asset revaluation and depreciation methods on the financial statements of PT Panca Putera Galvalum Steel. The depreciation methods examined include the straight-line method, the double-declining balance method, and the sum-of-the-years'-digits method. The results indicate that each depreciation method produces different depreciation expense values, thereby affecting the company's profit and the carrying amount of fixed assets. The double-declining balance method results in the highest depreciation expense, while the straight-line method produces the lowest depreciation expense. Furthermore, the revaluation of fixed assets reveals differences between the carrying amount and the fair value of the company's assets. Overall, both the depreciation methods and fixed asset revaluation have a significant effect on the company's financial statements, particularly on the value of fixed assets, depreciation expense, and company profit.